Propuesta de mejora del proceso productivo en la empresa Café Ismary del cantón Calvas, provincia de Loja 2022 - Tamayo Correa, Alexia Ainara (2023)
The objective of this research is to make a proposal for the improvement of production processes, based on Lean Manufacturing tools for the company Café Ismary located in the Calvas Canton of the province of Loja. A mixed approach was used, applying a qualitative study based on the collection of information through direct observation with the help of the production manager on the phases of coffee production and an interview with the general manager; a descriptive method was also used in which all the times, resources and materials used in the production process were detailed; The techniques implemented were the interview and direct observation, allowing a greater collection of information. An analysis was carried out on the seven Lean Manufacturing tools and two of them were applied, which were the 5 S and VSM (Value Chain Mapping). As a result, it was determined that with the implementation of the 5 S the proper placement of the roasting machine on the first floor was achieved and red cards were added to classify the unnecessary, warning signs were also placed on the first floor specifically in the fourth of production and an adequate production process will be carried out with the implementation of the flexible cell-Distribution in U, in addition there is an adequate cleaning area for personal hygiene, a cleaning checklist and yellow cards allowing to discard unnecessary things within the area/department, a board of standards for important communications was also placed and a 5 S checklist will be applied that will allow us to know if the proposal is being met. With the application of the VSM (Value Chain Mapping) it allowed the identification of idle times and unnecessary movements, information was collected on the monthly productive process (20 working days) that lasted 7,296 minutes (121 hours with 36 minutes) and with the implementation of the VSM proposal there was a decrease in times and movements in the four phases where a decrease of 2,071 minutes (34 hours and 31 minutes) was obtained, leaving 5,225 minutes (87 hours) as time of the monthly production process, working 4 hours daily with 21 minutes and 25 seconds for the transformation of an arroba of piled coffee (25 pounds).